Stunting Prevention through Local Wisdom of Mambosuri Culture in Pregnant Women of Batak Tribe - Natar Fitri Napitupulu; Anto J. Hadi; Khairunnisa Butar-Butar (Jurnal Keperawatan Priority, 2025)
Prevention of stunting in children was an important issue in efforts to improve the quality of human resources in Indonesia. Stunting could cause long-term impacts such as problems with physical growth, cognitive development, and productivity in adulthood. Therefore, preventing stunting in pregnant women is very important. The local wisdom of the Mambosuri culture of the Batak tribe in North Padang Lawas Regency can be an alternative in efforts to prevent stunting in pregnant women. This study aims to explore the use of local wisdom of Mambosuri to help prevent stunting in pregnant women of the Batak tribe in North Padang Lawas Regency. The research design is phenomenology. The data collection method was carried out by in-deptPrevention of stunting in children was an important issue in efforts to improve the quality of human resources in Indonesia. Stunting could cause long-term impacts such as problems with physical growth, cognitive development, and productivity in adulthood. Therefore, preventing stunting in pregnant women is very important. The local wisdom of the Mambosuri culture of the Batak tribe in North Padang Lawas Regency can be an alternative in efforts to prevent stunting in pregnant women. This study aims to explore the use of local wisdom of Mambosuri to help prevent stunting in pregnant women of the Batak tribe in North Padang Lawas Regency. The research design is phenomenology. The data collection method was carried out by in-depth interviews. The purposive sampling method was used to select participants who met the criteria as participants. The participants in this study numbered 7 people. The results of the transcribed interview were analyzed using content analysis. The results of this study found 4 themes that reflected the phenomenon being studied. These themes are the knowledge of pregnant women about the mambosuri tradition, the mambosuri tradition improves the nutritional status of pregnant women, the support that pregnant women receive from the mambosuri tradition, and the mamsbosuri tradition strengthens dalihan natolu kinship ties. h interviews. The purposive sampling method was used to select participants who met the criteria as participants. The participants in this study numbered 7 people. The results of the transcribed interview were analyzed using content analysis. The results of this study found 4 themes that reflected the phenomenon being studied. These themes are the knowledge of pregnant women about the mambosuri tradition, the mambosuri tradition improves the nutritional status of pregnant women, the support that pregnant women receive from the mambosuri tradition, and the mamsbosuri tradition strengthens dalihan natolu kinship ties.